LAMPROITES OF THE KARELIA-KOLA REGION - Proskuryakov V.V.; Uvadyev L.I.; Vionova O.A. (My University, 1990)
Detailed study of alkalic potassium-rich rocks of the Karelia-Kola region has revealed a rock group that fully satisfies petrographic, mineralogic and geochemical criteria for assigning it to the lamproite magmatic series. Our proposed classification of lamproites of the Karelia-Kola region is based on their quantitative mineralogic composition. Dividing these lamproites into species, and naming them from the principal rock-forming minerals we accordingly were able to identify five lamproite species.